ANALISIS KEMAMPUAN PEMAHAMAN KONSEP SISWA DALAM MENYELESAIKAN SOAL-SOAL MATEMATIKA KELAS VIII SMP NEGERI 23 REJANG LEBONG - Atma Nuraziz; Sukasno S.; Nur Fitriyana (LP4MK STKIP PGRI Lubuklinggau, 2020)
The purpose of this research is to describe students' concept comprehension ability in solving math problems in grade VIII of SMP Negeri 23 Rejang Lebong. This research uses descriptive qualitative method. The subjects in this study were grade VIII-1 students of SMP Negeri 23 Rejang Lebong which were divided into 3 groups, namely students with high ability, medium ability, and low ability. Data collection techniques in this study use test and interview techniques. The results showed that the percentage of achievement of each indicator of students' overall concept comprehension ability lies in the criteria of 56.67%. With the details of each concept understanding indicator as follows: 1) The indicator reasates a concept by 61.11%, 2) Indicators provide examples and not examples of 80.56%, 3) Indicators classify objects according to certain traits according to their concept of 40.74%, 4) Indicators present concepts in the form of mathematical representations of 53.24%, 5) Indicators develop necessary terms and conditions sufficient for a concept of 64.81 %, 6) Indicators using , utilizing and selecting certain procedures or operations by 40.28%, and 7) Indicators apply concepts or algorithms in troubleshooting by 66.20_%.